Analysis Of Electronic Medical Record Implementation To Improve Service Quality At Uki General Hospital - Ilyana Prasetya Hardyanti; Tri Budi W Rahardjo; Fresley Hutapea; Dinni Agustin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
Background: The development of information technology in the health sector encourages the implementation of Electronic Medical Records (EMR) to improve the efficiency and quality of hospital services. UKI General Hospital has implemented EMR, but still faces technical and operational challenges that hinder system optimization. Objective: This study aims to analyze the implementation of EMR at UKI General Hospital and evaluate its impact on the quality of hospital services. Method: The study used a mixed-method approach with data collection techniques through questionnaires, interviews, and quantitative and qualitative data analysis. The sample consisted of health workers and administrative staff involved in the use of EMR. Results: The results of the study indicate that the implementation of EMR has increased efficiency in patient data management, but there are still obstacles such as limited infrastructure, lack of HR training, and difficulties in adapting to technology. Conclusion: The implementation of EMR contributes to improving the quality of hospital services, but improvements are still needed in technical aspects and HR readiness. Suggestion: Improvements in infrastructure, medical personnel training, and strategic policies are needed to support more effective implementation of EMR.